Analysis of Human Resource Management Practices in Small and Micro Enterprises in Czech Republic - Lange, Elisabeth; Pauknerová, Daniela, 1970-; Bedrnová, Eva; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
This thesis analyses human resource management (HRM) practices in small and micro enterprises in the Czech Republic with the goal of developing recommendations for improvement of their HRM practices. The theoretical part provides background knowledge about small and micro enterprises in the Czech Republic, HRM in general and specifics of HRM in SMEs. It is followed by an elaboration on the three foci of this thesis: recruiting, training and development and retaining of qualified and experienced employees. Based on this theoretical fundament quantitative and qualitative research has been conducted in cooperation with Perfectia with the purpose of understanding the following: the HR function, what are the most challenging and time-consuming HR tasks for small and micro enterprises, how do they recruit, train & develop and retain employees and how important is HRM to small and micro enterprises. The hypothesis that most small and micro enterprises do not have formulated HR strategies (and if so aligned them with their business strategy) has been confirmed. The analysis and synthesis of the results from both the theoretical and empirical part are the basis, on which five key recommendations have been developed.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses